2014
DOI: 10.1364/boe.5.001941
|View full text |Cite
|
Sign up to set email alerts
|

Registration of adaptive optics corrected retinal nerve fiber layer (RNFL) images

Abstract: Glaucoma is the leading cause of preventable blindness in the western world. Investigation of high-resolution retinal nerve fiber layer (RNFL) images in patients may lead to new indicators of its onset. Adaptive optics (AO) can provide diffraction-limited images of the retina, providing new opportunities for earlier detection of neuroretinal pathologies. However, precise processing is required to correct for three effects in sequences of AO-assisted, flood-illumination images: uneven illumination, residual ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The increased ability to visualize and quantify these nerve fiber bundles, which have also been demonstrated in flood-illuminated ophthalmoscopes and SLO (Huang et al, 2012; Takayama et al, 2012, Ramaswamy et al 2014), have allowed for examination of differences in the bundles themselves and the observation that RNFL bundles possess a discrete reflectivity pattern. One study imaged the RNFL with AO-OCT in four healthy subjects and reported that the RNFL bundles reflect two times more light than the surrounding tissue (Kocaoglu et al, 2011a).…”
Section: The Expanding Role Of Ao-octmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased ability to visualize and quantify these nerve fiber bundles, which have also been demonstrated in flood-illuminated ophthalmoscopes and SLO (Huang et al, 2012; Takayama et al, 2012, Ramaswamy et al 2014), have allowed for examination of differences in the bundles themselves and the observation that RNFL bundles possess a discrete reflectivity pattern. One study imaged the RNFL with AO-OCT in four healthy subjects and reported that the RNFL bundles reflect two times more light than the surrounding tissue (Kocaoglu et al, 2011a).…”
Section: The Expanding Role Of Ao-octmentioning
confidence: 99%
“…Understandably, fundus cameras were the first imaging devices to implement AO technology in ophthalmology, as they employ simple optical principles involving little more than a camera capturing the light originating on the retina and emerging from the eye's optics to form an image on a light-sensitive film or charge coupled device. AO fundus cameras have since been used to image multiple structures in the eye, including photoreceptors (Lombardo et al, 2012), the RNFL (Ramaswamy et al, 2014) and retinal microvasculature (Popovic et al, 2011). …”
Section: Multimodal Imaging: Combining Ao-oct With Other Modalitiesmentioning
confidence: 99%
“…Adaptations of other methods may bridge this gap. 52 Further, ARFS performance has not been rigorously tested in image sequences where there is significant disruption to the cone mosaic such that ARFS may mistake aberrantly shaped or organized cones as being compressed or stretched. Subjectively, sampling a large strip of the retina typically makes the intraframe motion module robust to such disruptions, and tuning this parameter may resolve this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Algorithms that employ template-independent image quality metrics (e.g., sharpness, contrast, brightness) or statistical methods for automated reference frame selection from AO-flood, 5153 AO-LSO, 40 and AO-telescopes 54 have been proposed; however, these metrics are not robust for detecting motion artifacts within AOSLO images. Unsupervised registration algorithms of raw AO-flood image sequences have been developed, 55,56 however their efficacy in handling large motion artifacts has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…The NFL is a relatively strong source of back-scatter and its microstructure has been resolved with confocal AOSLO imaging (Huang et al 2014, Takayama et al 2012) and AO fundus cameras (Ramaswamy et al 2014). Fig.…”
Section: 0 State Of the Art In Ao Imaging Technologymentioning
confidence: 99%